Input modality and working memory: Effects on second language text comprehension in a multimedia learning environment. (December 2015) - Kozan, Kadir; Erçetin, Gülcan; Richardson, Jennifer C.
Abstract: This study investigated the modality effect in relation to verbal working memory capacity and time of testing within a computerized second language multimedia learning environment. Twenty-nine advanced learners of English with Turkish as the first language were randomly assigned to audiovisual or visual-only presentations about an unfamiliar topic and completed immediate and delayed tests to assess retention and transfer of information performance. They also completed a reading span test as a measure of working memory capacity. Results revealed a significant combined effect of time, input modality and working memory capacity on participants' retention performance while the only significant effect observed on transfer performance was that of time. Analyses on the significant three-way interaction revealed that although input modality and working memory capacity play some role in retention performance, their effects emerged dependent upon one other and time of testing.